A Calibration Study for Sensor-Based In-Season Nitrogen Management of Irrigated Winter Wheat - Erdinc Savaşlı; Oğuz Önder; Ramis Dayıoğlu; Didem Özen; Suat Özdemir; Yaşar Karaduman; Özgür Ateş; Melih Özsayın (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted at Transitional Zone Agricultural Research Institute in Eskisehir, in 2017-2019 growing seasons. In the study, responses of four winter wheat cultivars (Atay85, Hat 31, Yunus and Nacibey) to nitrogen fertilization under irrigation conditions were compared with vegetation indices based on spectral reflection and In- Season Estimates of Yield calculated from these indices. GreenSeekerTM (NTech Industries, Inc., Ukiah,CA) hand-held sensor was used for this purpose. The experimental layout were used 0, 4, 8, 12, 16 and 20 kg N/da nitrogen rates 2 factor factorial in randomized complete block design in the experiment. Vegetation indices (NDVI) were obtained at growth stages Zadoks2,4, Zadoks3,0, Zadoks3,1 and Zadoks3,2. Zadoks3,0 (stem elongation) was found to be the most realistic reading time. A comparison of the system with traditional farmer applications, based on the average of 3 experiment fields, the new system was shown to give similar yields with 2,8 kg/da less N in the spring (ZD3,0), showing its economically promising value. The sensor application is determined to be 2% more economically effective than farmer application. Economic nitrogen dose respectively Atay85, Hat 31, Yunus and Nacibey was determined as the nitrogen dose 12,6 kgN/da, 14,1 kgN/ da, 14,4 kg N/da and 17,9 kgN/da.